PENGEMBANGAN EKONOMI LOKAL MELALUI PEMBERDAYAAN EKONOMI PEREMPUAN (Studi Pada Desa Candi Renggo Kecamatan Singosari Kabupaten Malang) - Fitriyah Fitriyah; Esy Nur Aisyah; Putri Kurnia Widiati (Pusat Studi Gender UIN Maulana Malik Ibrahim Malang, 2016)
Singosari is a town in Malang, East Java province, Indonesia. The subdistrict is located in the North of Malang city, district is crossed the main line of Surabaya-Malang and included as the worst jam region point in Malang. But from the human resources side, Singosari is arguably one of the most advanced sub top and most popular in Malang. Located at an altitude of 400-700 meters. Singosari district having a cool climate. Higher areas were located in Western foot of Arjuno mountain where most of its territory destined for plantations (coffee), forestry (mahogany) and livestock (chickens). Along with Lawang and Kepanjen, Singosari was known as satellite city of Malang main buffer, which is included in the area of Malang raya.This research is applied research (Applied Reseach) i.e. research that had practical reasons, desire to know which aims to be able to do something better, effective, efficient. Research conducted for the purpose to applying the results in order to solve a particular problem that is being experienced by an organization. This type of research is a qualitative with descriptive approach.Based on the results of the analysis undertaken in the development of the local economy based on trade and superior commodities sector's in the village of Candirenggo Kec. Singosari, we can get the conclussion as follows: Superior commodity trading sectors in the village Candirenggo Kec. Singosari is for food crop subsector is Red Ginger. The development of commodity can be done through an increase in variation products processing to create added value. In addition, it needs to be seen to cluster industry development opportunities to enhance the competitiveness of the superior commodity (Red Ginger).Singosari adalah sebuah kecamatan di Kabupaten Malang, Provinsi Jawa Timur, Indonesia. Kecamatan ini berada di sebelah utara Kota Malang, kecamatan ini dilintasi jalur utama Surabaya-Malang dan termasuk sebagai daerah titik macet terparah di Malang. Namun dari sisi SDM Singosari dapat dikataka sebagai salah satu dai urutan teratas kecamatan termaju dan paling terpandang di Kabupaten Malang. Terletak pada ketinggian 400-700 meter . DPL, Singosari beriklim sejuk. Daerah yang lebih tinggi berada di sebelah barat kaki Gunung Arjuno dimana sebagian besar wilayahnya diperuntukkan bagi perkebunan (kopi), kehutanan (mahoni) dan peternakan (ayam). Bersama dengan Lawang dan Kepanjen, Singosari dikenal sebagai kota satelit penyangga utama Kota Malang, yang termasuk dalam kawasan Malang raya Penelitian ini merupakan jenis penelitian terapan (Applied Reseach) yaitu penelitian yang mempunyai alasan praktis, keinginan untuk mengetahui yang bertujuan agar dapat melakukan sesuatu yang lebih baik, efektif, efisien. penelitian yang dilakukan dengan tujuan untuk menerapkan hasil penemuan guna memecahkan masalah tertentu yang sedang dialami suatu organisasi. Jenis penelitian ini adalah kualitatif dengan pendekatan deskriptif. Berdasarkan hasil analisis yang dilakukan dalam pengembangan ekonomi lokal berdasarkan sektor perdagangan dan komoditas unggulan di Desa Candirenggo Kec. Singosari diperoleh kesimpulan sebagai berikut:Komoditas unggulan sektor perdagangan di Desa Candirenggo Kec. Singosari adalah untuk subsektor tanaman bahan makanan adalah Jahe Merah. Pengembangan komoditas dapat dilakukan melalui peningkatan variasi produk hasil pengolahan untuk menciptakan nilai tambah. Disamping itu, perlu dilihat peluang pengembangan klaster industri untuk meningkatkan daya saing dari komoditas unggulan (Jahe Merah).